Harnessing forestry potentials in actualizing National economic empowerment development strategy (2005)
National Economic Empowerment Development Strategy (NEEDS) is a development plan that integrates economic development efforts at the Federal, State and Local Government levels. Its vision, values and principles are encapsulated by four goals: Wealth creation; Employment generation; Poverty reduction, and Value reorientation, with the “modus-operandi” for achieving these goals being anchored on three main strategies; viz; empowering people, promoting private enterprises and changing the way government does its work. The Nigerian forestry sector which has the responsibility to sustainably develop and manage about 25% of Nigerian land mass, to meet the diverse needs of the teeming urban and rural population; no doubt has a salient role to play in achieving the goal of NEEDS. Some of these roles include provision of comprehensive databases, promotion of forest based small scale enterprises, crafting institutional framework for boosting wood production and biodiversity conservation, restructuring the forestry- industrial sector, establishment of ministry of renewable natural resources and crafting institutional framework for sustainable urban forestry development. Collaborative efforts of FDF, FAN and other stakeholders to garner political support and networking for effective advocacy, are essential for forestry optimal contribution to NEEDS.